Corporate Social Responsibility And Tax Avoidance: Evidence From Korean Firms - Park, SungJong (Journal of Applied Business Research, 2017)
This study examines the relationship between corporate socially responsible (CSR) activities and tax avoidance using residual book-tax differences (BTD), year residual BTD and total BTD. Using a sample of 1,148 publicly listed Korean firms on Korean Stock Exchange (KSE) covering periods between 2004 and 2009 it finds that the firms with higher CSR activities are less likely to avoid taxes regardless which proxy of tax avoidance is used. This finding is confirmed with two stage least square (2SLS) method after accounting for endogeneity of CSR. It also tests how seven different CSR activities affect tax avoidance, and finds that social services, satisfaction of employees and contributions to economic development are negatively related to tax avoidance. Overall, the empirical results of this paper support the previous studies arguing the negative relationship between tax avoidance and CSR.
Keywords: Tax Avoidance; Corporate Social Responsibility; Book-Tax Differences